Naming Moroccan fish: when diversity faces standardisation imperatives. (3rd June 2016) - Masski, H.; Ait Hammou, A.
Summary: The Moroccan national fisheries information system aims at adopting a standard list of common names for fishery products. Thus, the goal of this study is to provide a means structuring vernacular names, which, although in wide use, are highly variable and do not necessarily meet trade requisites. The 138 species considered in this study have 691 vernacular names – an average of five names per species. Large disparities in the number of vernacular names were found between species and among the 16 study sites. Much of this variability is due to pronunciation and syllable adjunction, which do not affect the root name structure. Pronunciation aside, for the most part the analysed variability in vernacular names of fishes is of linguistic origin stemming from four geographic – and thus cultural – groups. The Iberian names, preponderant in the eastern Moroccan Mediterranean, decreased southward in favour of Arabic, Amazigh and French. According to these results, the adoption of a unique standard, if even possible, might encounter resistance to dissemination by the fishermen and local populations. The adoption of two names lists, one for the Moroccan Mediterranean and one for the Moroccan Atlantic, may be a good compromise. Most efforts at standardisation should then be invested at fish markets in order to integrate fish identification and labelling processes prior to selling.